Katechumenat jako droga do dojrzałości chrześcijańskiej na kolejnych etapach rozwoju człowieka - Andrzej Jastrzębski (Wrocławski Przegląd Teologiczny)
From the very beginning of the Church’s history the catechumenal pedagogy played a crucial role. Its aim is to foster the development of mature Christians able to show concrete signs of conversion, i.e. trust in God and love of ene mies. There were times when catechumenate was abandoned but in the most important periods of Church’s history it was fully bloomed. The pedagogy of catechumenate is based on quite simple principles: the Word of God, liturgy, and community. This pedagogy leads a candidate for baptism or an already baptized person to be able to fully receive the grace of it, which is the surrender to God’s love and forward it into the world where he or she lives. The pedagogy of catechumenate seems to be universal and applicable for many purposes: for religious education and formation, for reviving faith, for new evangelization and for reinforcing a believer on different stages of human development over time.